PERBANDINGAN PENDAPATAN USAHATANI CAMPURAN BERDASARKAN PENGELOMPOKAN JENIS TANAMAN - Jefier Andrew Kuheba; Joachim N.K. Dumais; Paulus A. Pangemanan (Sam Ratulangi University, 2016)
The objective of research is to compare how much the average income per hectare of farms mixture by grouping types of plants in the Airmadidi Bawah Village. This research was conducted in the Airmadidi Bawah urban village for 3 months, from September to November 2015 with the method of data collection by using primary data. Samples taken were 15 for each farming mix using cluster random sampling technique. To determine the ratio mix used farm income analysis tool SPSS by using t-test. The results showed that there were significant differences between 1st mixed farming with 2nd mixed farming; the average income per hectare of 1st mixed farming Rp. 35.921.389,- was higher than the average income per hectare of 2nd mixed farming Rp. 30.430.699,- Results of testing the hypothesis 1st mixed farming and 2nd mixed farming shows the t-test (4.910) > t-table (1,761). From the test results, Ho is rejected and H1 is accepted, it means that there are differences in the average income per hectare of the 1st mixed farming and 2nd mixed farming.jnkd